Treatment of a pediatric recurrent fusiform middle cerebral artery (MCA) aneurysm with a flow diverter. (16th November 2012) - Burrows, Anthony M; Zipfel, Gregory; Lanzino, Giuseppe
Abstract : Pediatric patients with aneurysm often have different localizations and morphologies from adults and recurrences are not uncommon after successful clip reconstruction/obliteration. Treatment of a recurrent pediatric aneurysm after clip ligation is a technical challenge. We present the case of an adolescent with a middle cerebral artery (MCA) fusiform aneurysm which recurred following clip reconstruction and bypass. The aneurysm was successfully treated with endovascular flow diversion.